Penerapan Metode Drill dalam Membaca Notasi pada Lagu BE.No 6 Puji Jahowa Nasangap di HKBP Dolok Margu Resort Dolok Sanggul - Yoktan Manutur Silaban; Roy J M Hutagalung; Diana Martiani Situmeang; Eben H. Telaumbanua; Robert K.A. Simangunsong (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The purpose of this study was to determine the progress of the repeated practice sessions in reading notation according to the predetermined practice schedule and to find out the problems in implementing the practice activities faced by HKBP Dolok Margu musicians.This study uses a Qualitative Approach Method. The work processes carried out are observation, interviews, documentation. This study was conducted by collecting information through field research to obtain results that are processed into definite data.The results of the conclusion of this study are that the Application of the Drill Method in Reading BE.NO 6 Notation at HKBP Dolok Margu Resort Dolok Sanggul has experienced significant changes.This is indicated by the consistency of the practice process carried out on Thursdays and Fridays at 16:00 to 18:30, musicians from the Dolok Margu area, reading number notation and staff notation and habits of each service, the congregation's response liked after the drill method was carried out in reading notation at HKBP Dolok Margu.